تقنيات معالجة المياه المصاحبة لانتاج النفط (دراسة حالة -حقل النافورة النفطي) - منال سالم علي أبومداس الفيتوري (The Libyan Journal of Science, 2024)
Water treatment technologies associated with oil production are crucial in the oil and gas industry, as they require the removal of various contaminants and impurities before they can be safely disposed of or reused. Technologies used in treating associated water include processes such as oil and grease removal, removal of solid impurities and suspended sediments, and chemical separation to remove organic and mineral contaminants. Biodisinfection techniques can also be used to eliminate organic plankton and biological contaminants. Using these techniques, oil-based water can be effectively purified and reused or disposed of in environmentally friendly ways. This paper aimed to study the current situation in the Nafoora oil field of the Arabian Gulf Oil Company, where the produced quantities of associated water and methods of dealing with it were monitored, and some physical and chemical properties of this water were studied, where some parameters were measured, which included measuring salinity TDS and temperature, acidity pH, electrical conductivity Ec., Calcium Ca+2 and Magnesium Mg+2, Sodium Na+, Sodium Adsorption Ratio -SAR, Nitrate NO3- and Sulfate. The results of the study showed that the pH value of the associated water ranged between 4.2 and 7.6, while the Total Dissolved Solids (TDS) ranged between 53965 mg/l and 98634 mg/l, while Nitrate concentrations ranged from 243 mg/l to 642 mg/l. The paper also reviewed some treatment methods for produced associated water, which can be applied locally and ways to benefit from them, which include chemical treatment, filtration and phase separation.